PROPOSED METHODOLOGY FOR INDONESIAN STATE- OWNED ENTERPRISE TO CONDUCT CORPORATE SPIN- OFF - Pasca, Adrian
This research addresses a critical gap in the corporate landscape by proposing a comprehensive methodology for Indonesia State-Owned Enterprises (SOEs) to conduct corporate spin-offs, focusing on the aviation sector as a real business issue. The absence of a formal framework for state-owned enterprises to execute spin-offs necessitates a structured approach that considers regulatory compliance, business law, and procedural requirements.